Comparative study: International chain and local chain hotel COVID-19 readiness strategies in Indonesia - Yoanita Alexandra; Purnamaningsih Purnamaningsih; Septi Fahmi Choirisa (Economics, Management and Sustainability)
The global hospitality and tourism industry has been severely impacted by the spread of COVID-19 and large-scale travel restrictions. Due to the nature of the crisis of COVID-19, Hotel businesses in Indonesia need to adapting many new strategies in response to the evolving circumstances. This study presents a comparative coronavirus readiness strategy at International Chain Hotel and Local Hotel in Indonesia and their impacts on hotel guests’ trust and satisfaction. The study used quantitative approaches by using an online survey to obtain data from a total of 400 participants. The data were collected from respondents that have been stayed in both the International Chain hotel or Local Chain Hotel in Indonesia during pandemics. The data collected is analyzed using Structural Equation Modeling (SEM) with Smart PLS statistical software. The findings from this dataset show that both local and international hotel readiness had a significant effect on customer trust and satisfaction with COVID-19 readiness in the hotel industry.